2017
DOI: 10.1002/pros.23452
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs and treatment response in the Phase II SWOG S0925 study for patients with new metastatic hormone‐sensitive prostate cancer

Abstract: Baseline plasma miR-141, miR-200a, and miR-375 levels are associated with baseline CTC count. Baseline miR-375 was also associated with the trial endpoint of 28-week PSA response. Our results provide evidence that circulating miRNA biomarkers may have value as prognostic biomarkers and warrant further study in larger prospective clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…It has been shown that exosome isolation from liquid biopsies improves the sensitivity of miRNA amplification and detection [53]. Cumulating data suggest that miRNAs have potential as diagnostic and/or prognostic biomarkers in PCa [55][56][57][58][59]. Several miRNAs have been studied in plasma and serum of mCRPC patients.…”
Section: Circulating Nucleic Acidsmentioning
confidence: 99%
“…It has been shown that exosome isolation from liquid biopsies improves the sensitivity of miRNA amplification and detection [53]. Cumulating data suggest that miRNAs have potential as diagnostic and/or prognostic biomarkers in PCa [55][56][57][58][59]. Several miRNAs have been studied in plasma and serum of mCRPC patients.…”
Section: Circulating Nucleic Acidsmentioning
confidence: 99%
“…The miRNA signatures are also helpful in determination of the primary site in tumors of unknown origin (22)(23)(24). Use of the miRNAs as blood-based markers has tremendous potential when used in combination with the existing PSA screening techniques for the status of the disease-cancer or not (25)(26)(27), and course of treatment (28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of gene and miRNA biomarkers for both the early detection and prognosis of PC is a current challenge. However, currently, there are only few clinical trials with such purposes [ 99 , 100 , 101 ]. We hypothesized that gene and miRNA signatures of PC could be found by identifying sub-pathways of co-regulated genes that are targeted by specific miRNAs.…”
Section: Discussionmentioning
confidence: 99%